Adaptive exhaustion during prolonged intermittent hypoxia causes dysregulated skeletal muscle protein homeostasis. (10th January 2023) - Attaway, Amy H.; Bellar, Annette; Mishra, Saurabh; Karthikeyan, Manikandan; Sekar, Jinendiran; Welch, Nicole; Musich, Ryan; Singh, Shashi Shekhar; Kumar, Avinash; Menon, Aishwarya; King, Jasmine; Langen, Ramon; et al.
Abstract : Abstract: Nocturnal hypoxaemia, which is common in chronic obstructive pulmonary disease (COPD) patients, is associated with skeletal muscle loss or sarcopenia, which contributes to adverse clinical outcomes. In COPD, we have defined this as prolonged intermittent hypoxia (PIH) because the duration of hypoxia in skeletal muscle occurs through the duration of sleep followed by normoxia during the day, in contrast to recurrent brief hypoxic episodes during obstructive sleep apnoea (OSA). Adaptive cellular responses to PIH are not known. Responses to PIH induced by three cycles of 8 h hypoxia followed by 16 h normoxia were compared to those during chronic hypoxia (CH) or normoxia for 72 h in murine C2C12 and human inducible pluripotent stem cell‐derived differentiated myotubes. RNA sequencing followed by downstream analyses were complemented by experimental validation of responses that included both unique and shared perturbations in ribosomal and mitochondrial function during PIH and CH. A sarcopenic phenotype characterized by decreased myotube diameter and protein synthesis, and increased phosphorylation of eIF2α (Ser51) by eIF2α kinase, and of GCN‐2 (general controlled non‐derepressed‐2), occurred during both PIH and CH. Mitochondrial oxidative dysfunction, disrupted supercomplex assembly, lower activity of Complexes I, III, IV and V, and reduced intermediary metabolite concentrations occurred during PIH and CH. Decreased mitochondrial fission occurred during CH. Physiological relevance was established in skeletal muscle of mice with COPD that had increased phosphorylation of eIF2α, lower protein synthesis and mitochondrial oxidative dysfunction. Molecular and metabolic responses with PIH suggest an adaptive exhaustion with failure to restore homeostasis during normoxia. Key points: Sarcopenia or skeletal muscle loss is one of the most frequent complications that contributes to mortality and morbidity in patients with chronic obstructive pulmonary disease (COPD). Unlike chronic hypoxia, prolonged intermittent hypoxia is a frequent, underappreciated and clinically relevant model of hypoxia in patients with COPD. We developed a novel, in vitro myotube model of prolonged intermittent hypoxia with molecular and metabolic perturbations, mitochondrial oxidative dysfunction, and consequent sarcopenic phenotype. In vivo studies in skeletal muscle from a mouse model of COPD shared responses with our myotube model, establishing the pathophysiological relevance of our studies. These data lay the foundation for translational studies in human COPD to target prolonged, nocturnal hypoxaemia to prevent sarcopenia in these patients. Abstract : Abstract figure legend Prolonged intermittent hypoxia (PIH) is commonly demonstrated in patients with COPD (chronic obstructive pulmonary disease); however, the effects of PIH on skeletal muscle are unclear. We tested the hypothesis that PIH causes skeletal muscle loss or sarcopenia in vitro by downregulating protein synthesis and causing mitochondrial oxidative dysfunction associated with dysregulation of hypoxia‐inducible factors (HIF1α and HIF2α). α‐Ketoglutarate (αKG), a critical tricarboxylic acid cycle intermediate and co‐factor for the degradation of HIF1α, was reduced due to PIH. Physiological relevance was established in skeletal muscle of mice with COPD. Our findings suggest that PIH causes sarcopenia through adaptive exhaustion and failure to restore homeostasis during normoxia.